Media Digital sebagai Instrumen Pembelajaran Agama: Perspektif Komunikasi Budaya dalam Pendidikan Islam - Untung Famuji; Eri Syahriyah (Advances In Education Journal, 2025)
This study explores the role of digital media as an instructional instrument in Islamic education through the lens of cultural communication. The research addresses the global transformation of Islamic pedagogy in the digital era, where online platforms, social media, and virtual learning spaces increasingly shape religious learning experiences. The objective is to analyze how digital media function not only as tools for transmitting religious knowledge but also as spaces of intercultural negotiation within Muslim societies worldwide. Employing a qualitative, interpretive approach with multi-case study design, this research examines digital Islamic learning platforms in Indonesia, Egypt, the United Kingdom, and Malaysia through content analysis, interviews, and participatory observation. The findings reveal that digital media foster new forms of transnational Islamic identity, promote interactive and participatory religious engagement, and create hybrid learning models that blend traditional and contemporary pedagogical approaches. However, challenges related to religious authority, content authenticity, and cultural adaptation require careful attention. The study concludes that integrating digital media into Islamic education requires a communication model rooted in cultural sensitivity and dialogic pedagogy, ensuring technology serves as an enabler of spiritual growth, critical thinking, and ethical reflection while respecting diverse interpretations across Muslim communities.